2018
DOI: 10.1080/24749508.2018.1452478
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of forest cover dynamics in eastern area of Béni-Mellal Province using ASTER and Sentinel-2A multispectral data

Abstract: This study aimed to monitor and analyze the spatial and temporal dynamic of forest cover in Eastern area of Beni-Mellal Province (Morocco), using multispectral ASTER and Sentinel-2A MIS images acquired in 2001 and 2015, respectively. The supervised classification algorithm and NDVI were combined within a GIS environment to quantify the extent and density change of forest cover stands, i.e., Holm oak, Aleppo pine, Thya, Zea oak, Crops & others and Bare ground. The classification overall accuracy was 97.76 and 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 44 publications
1
34
0
Order By: Relevance
“…• Under the condition of sub-soiling, the wetting body formed by point source infiltration under drip irrigation is a semi ellipsoid. The larger the dripper discharge, the flatter the ellipsoid; with the increase of irrigation time, the wetting body is close to the hemisphere, and the distribution of salt and alkali is consistent with the distribution of wetting body [33]. irrigation duration, both horizontal and vertical salinity increased, while both horizontal and vertical salinity decreased with the increase of distance from emitter [34].…”
Section: Discussionsupporting
confidence: 53%
“…• Under the condition of sub-soiling, the wetting body formed by point source infiltration under drip irrigation is a semi ellipsoid. The larger the dripper discharge, the flatter the ellipsoid; with the increase of irrigation time, the wetting body is close to the hemisphere, and the distribution of salt and alkali is consistent with the distribution of wetting body [33]. irrigation duration, both horizontal and vertical salinity increased, while both horizontal and vertical salinity decreased with the increase of distance from emitter [34].…”
Section: Discussionsupporting
confidence: 53%
“…Previous studies have successfully been carried out using remote sensing geospatial tools in a related study at the same profile area. For example, Barakat et al [20] have used ASTER (Advanced Spaceborne Thermal Emission and Reflection Radiometer) and Sentinel-2A MSI images, acquired in 2001 and 2015 respectively, for quantifying the changes in the Eastern area of Béni-Mellal province based on the supervised classification algorithm and the normalized difference vegetation index (NDVI). The study showed that changes in land use have resulted in the increase of forest area.…”
Section: Discussionmentioning
confidence: 99%
“…Mapping areas of forest cover change is essential for developing locally adapted strategies to better control these dynamics (de Wasseige et al 2014). Remote sensing has proven to be an essential low-expensive and effective technology for determining land cover and land use dynamics over several decades and at different scales (Loveland and Dwyer 2012;Hansen et al 2013;Wani et al 2016;Mukete et al 2017;Barakat et al 2018). One of the first steps in implementing REDD þ is the estimation and monitoring of carbon stocks in different land-use.…”
Section: Introductionmentioning
confidence: 99%